2009
DOI: 10.1088/0266-5611/25/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gradient projection methods for edge-preserving removal of Poisson noise

Abstract: Several methods based on different image models have been proposed and developed for image denoising. Some of them, such as total variation (TV) and wavelet thresholding, are based on the assumption of additive Gaussian noise. Recently the TV approach has been extended to the case of Poisson noise, a model describing the effect of photon counting in applications such as emission tomography, microscopy and astronomy. For the removal of this kind of noise we consider an approach based on a constrained optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
169
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 30 publications
2
169
1
Order By: Relevance
“…Then, [43] showed that, for large λ: In the case of deconvolution, we have y = P(Hx + b) and thus y is a Poisson random variable with mean Hx + b. So, from this statement and (43), [43] defined:…”
Section: A State Of Artmentioning
confidence: 95%
See 2 more Smart Citations
“…Then, [43] showed that, for large λ: In the case of deconvolution, we have y = P(Hx + b) and thus y is a Poisson random variable with mean Hx + b. So, from this statement and (43), [43] defined:…”
Section: A State Of Artmentioning
confidence: 95%
“…Finally, we would like to mention also the recent work of Bertero et al [43] in which is introduced a discrepancy principle for Poisson noise. First, let us consider the following function:…”
Section: A State Of Artmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to fully define the SPDHG method, we focus on the strategy to compute a suitable scaling matrix D k , adapting to our case the split gradient strategy proposed in [1] for nonnegatively constrained differentiable problems, which demonstrated to be very effective in several applications (see [16,6] and references therein). The key point of this approach consists in finding a subgradient decomposition of the form…”
Section: Endmentioning
confidence: 99%
“…In [24] (see also [3]) statistical arguments were used to show that τ I = 1 2 n is a good estimate in case of moderate Poisson noise. In [5] this estimate was improved in case f has many zero components.…”
Section: Primal-dual Algorithmsmentioning
confidence: 99%